2001
DOI: 10.1046/j.1468-1293.2001.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

MIKADO: a multicentre, open‐label pilot study to evaluate the antiretroviral activity and safety of saquinavir with stavudine and zalcitabine

Abstract: BackgroundSince eradication of HIV is unlikely, long-term management of the disease necessitates careful evaluation of the combinations of currently available drugs to determine the most potent and useful rational sequencing of regimens. ObjectiveTo determine the antiretroviral ef®cacy and tolerability of saquinavir soft gelatin capsule (SQV-SGC) plus zalcitabine (ddC) and stavudine (d4T), as ®rst-line treatment in HIV-infected patients. DesignMulticentre, open-label, non-comparative study. Patients and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…ddI+d4T combination was associated with an almost two-fold increase in the relative risk of PN, as assessed by Poisson regression. These data are similar to other reports (Katlama et al, 2001;Reliquet et al, 2001). The usage of other NRTIs such as zidovudine, zalcitabine and lamivudine did not appear to increase the risk of developing PN.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ddI+d4T combination was associated with an almost two-fold increase in the relative risk of PN, as assessed by Poisson regression. These data are similar to other reports (Katlama et al, 2001;Reliquet et al, 2001). The usage of other NRTIs such as zidovudine, zalcitabine and lamivudine did not appear to increase the risk of developing PN.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that PN is more frequent when didanosine and stavudine are used in combination (Katlama et al, 2001;Lea & Faulds, 1996). Thus, we designed a similar analysis to assess the relative risk of PN.…”
mentioning
confidence: 99%
“…Katlama et al evaluated the antiretroviral efficacy and tolerability of the PI, saquinavir soft gelatin capsule (SQV-SGC) + zalcitabine (DDC) and STV, as first-line treatment in HIV-infected patients (MIKADO trial) [44].…”
Section: Triple Drug 2-class Therapymentioning
confidence: 99%
“…18,[72][73][74][75][76] In a recent study of 212 patients receiving PI-based ART, RTVand LPV/RTV-containing regimens caused the highest incidence of hypercholesterolemia and hypertriglyceridemia after 12 months of therapy. 72 These data were confirmed in a study of 353 previously treated patients who received LPV/RTV treatment.…”
Section: Early Pismentioning
confidence: 99%